Nature Policies and Landscape Policies Towards an Alliance - Gambino, Roberto (Springer, 2015)
Since the beginning of the 1990s, the European Documentation Centre on Nature Park Planning (CED PPN, DIST, Politecnico and Universita ` di Torino) has conducted ongoing research into nature and heritage conservation policies and their relationship with urban and regional planning. Particular attention has been given both to European parks and other protected area1 policies and to European landscape2 policies...